SALMONELLA TYPHIMURIUM VACCINE TO CONTROL A BRAZILIAN SALMONELLA HEIDELBERG STRAIN IN BROILER CHICKENS - HAYASHI, R. M.; TUJIMOTO-SILVA, A.; MUNIZ, E. C.; VERDI, R.; SANTIN, E. (Ars Veterinaria, 2018)
Foodborne Salmonella infections in humans, which results from the consumption of contaminated poultry meat and eggs, are a major public health concern. Vaccination of animals against Salmonella is one strategy to prevent these infections and reduce the risks to public health. Live attenuated Salmonella enterica vaccines can confer protection against salmonellosis by inducing both cell-mediated and mucosal immune responses. This study assessed a live, attenuated Salmonella enterica Typhimurium (ST) vaccine in broiler chickens against a heterologous challenge with Salmonella Heidelberg (SH) by evaluating bacterial quantification, immune cells infiltration, and cytokine gene expression in the cecum. The treatments were: T1, non-vaccinated, non-challenged; T2, non-vaccinated, SH-challenged; T3, ST-vaccinated and SH-challenged. At 28 days of age, the ST-vaccinated group had significantly recovered reduction of SH in the crop (P<0,01) and cecum (P = 0,021) compared to the non-vaccinated SH-challenged group, with no significant changes (P˃0,05) in macrophages, T CD4+, or T CD8+ cells dynamics during the same period. Aerosol vaccination on the first day promoted greater interleukin-12 expression in the liver (P<0,.05) and interleukin-10 expression and T CD8+ cells in the ileum 16 hours after housing. After prime-boosted oral immunization on the 13th day, the vaccinated group had greater expression of macrophages and T CD4+ cells in the liver (P<0,05) than the control group. Two doses of a live ST-attenuated vaccine promoted a partial cross-protective effect against SH strain UFPR1 challenge in broilers.